How Festival Experience Quality Influence Visitor Satisfaction? A Quantitative Approach - Marković, Suzana (Naše gospodarstvo/Our economy, 2019)
The purpose of research presented in this paper is to determine how selected characteristics of a city event affect the satisfaction of visitors. In particular, the aim is to identify factors related to event atmospherics that determine visitor satisfaction in the city destination in continental part of Croatia. For this purpose, questionnaire was created based on previously conducted research by Bitner (1992), Oliver (1980, 1997), Baker and Crompton (2000), and Lee, Lee, Lee, and Babin (2008). It comprised measures for assessing event atmospherics, visitor satisfaction, and demographic characteristics of the respondents. The research was conducted among visitors of a city event that takes place every year during December 2018. A total of 191 questionnaires were obtained during the one- month period. Principal component analysis was utilised to determine the factor structure of city event atmospherics. In addition, multiple regression analysis was conducted to determine which factors may serve as predictors of visitor satisfaction in city event context. As a result, the analyses revealed four factors related to city event atmospherics. In addition, these factors positively and significantly affected visitor satisfaction, indicating that they have important role in determining visitor satisfaction in a city event context. These findings can contribute to the knowledge advancement of the city events, their influence on tourist satisfaction, and consequently, to better understand specific groups of visitors as well as establish efficient marketing and promotion strategies.